STRATEGI PENYALURAN PUPUK BERSUBSIDI DI INDONESIA - Ragimun, Ragimun; Makmun, Makmun; Setiawan, Sigit (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
o realize food self-sufficiency in Indonesia, it needs to be supported by effective distribution of subsidizedfertilizer. The main causes of ineffective distribution of subsidized fertilizers are irregularities, weak oversightfrom implementing institutions and weak community control. Likewise, the aspects of transparency andinformation disclosure in the chain of subsidized fertilizer implementation are also still weak. So far, theregulations governing the mechanism for implementing subsidized fertilizer distribution policies are quiteadequate but their implementation is still weak. In this study a descriptive approach is used to explore anddescribe the development of distribution as well as the strategies adopted to obtain more effective alternativedistribution of subsidized fertilizer. This study also compares the policy of distribution of subsidized fertilizersin several countries. Based on the results of the study, several schemes or alternative distribution of subsidizedfertilizer are still needed in Indonesia. Irregularities occur because of errors in the collection of data